1999
DOI: 10.1021/jo990105o
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Hydrolysis of α-Oxo Carboxylic Acid Derivatives and Conjugate Addition to α,β-Unsaturated Carbonyl Compounds:  A Density Functional Study

Abstract: Hydration of the keto group as well as hydrolysis (ester and amide) of alpha-oxo carboxylic acid derivatives has been studied by density functional theory (B3LYP/6-31G and B3LYP/6-311G). Both uncatalyzed as well as water-assisted processes have been considered. Solvent effects were approximated by the self-consistent isodensity surface polarized continuum (SCIPCM) model. For hydrolysis reactions a concerted as well as a stepwise mechanism was calculated. In the latter one, addition of the nucleophile to a tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Cyclic transition-state structures are frequently postulated in the literature, [4][5][6]9,10 including for proton transfer in water 12,28 and acid-12 and base-catalyzed [10][11][12] hydrolysis of esters. In pure water or in water-rich solvent mixtures, water-to-water hydrogen bonds predominate and a multiple number of protons participate in the transition state for the hydrolysis of p-methylphenyl trichloroacetate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic transition-state structures are frequently postulated in the literature, [4][5][6]9,10 including for proton transfer in water 12,28 and acid-12 and base-catalyzed [10][11][12] hydrolysis of esters. In pure water or in water-rich solvent mixtures, water-to-water hydrogen bonds predominate and a multiple number of protons participate in the transition state for the hydrolysis of p-methylphenyl trichloroacetate.…”
Section: Resultsmentioning
confidence: 99%
“…For example, reaction of p-nitrophenyl trifluoroacetate is thought to proceed with three protons undergoing bonding changes in an eight-membered transition state (1). 4 A great number of both experimental [4][5][6][7][8] and theoretical [8][9][10][11][12] studies have been devoted to the hydrolysis reactions of aldehydes, ketones, esters and amides. [13][14][15][16][17] It has been observed that the nucleophile attack on a carbonyl group is mediated by water molecules that previously hydrated the carbonyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in comparison with the wide availability of empirical works, relatively few computational approaches have addressed the hydrolysis of esters. In the case of lactone hydrolysis, the disproportion is even larger, computational works being especially scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] This process can be understood as a competition between EWGs on either side of the activated double bond. For example, reactions of dimethylamine or methanol with methyl 3,3-bis(trifluoromethyl)propenoate (8) give the corresponding α-adducts, [13] as do additions of thiols to 2,4-dinitro-(e.g., 24) and 2,4,6-trinitrocinnamates. [14] Phosphane-catalyzed reaction of nitrogen nucleophiles with 2-alkynoates redirects the regioselectivity of ad-respect to properties of the substituents.…”
Section: Introductionmentioning
confidence: 99%